1995
DOI: 10.1136/thx.50.6.620
|View full text |Cite
|
Sign up to set email alerts
|

Mouth pressure in response to magnetic stimulation of the phrenic nerves.

Abstract: Background -Diaphragm strength can be assessed by the measurement of gastric (Tw PGA), oesophageal (Tw POES), and transdiaphragmatic (Tw PDI) pressure in response to phrenic nerve stimulation. However, this requires the passage of two balloon catheters. A less invasive method of assessing diaphragm contractility during stimulation of the phrenic nerves would be of clinical value. A study was undertaken to determine whether pressure measured at the mouth (Tw PM) during magnetic stimulation ofthe phrenic nerves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 14 publications
5
62
1
Order By: Relevance
“…In a preliminary study, we compared Poes,tw, considered as reference, to three noninvasive measurements of inspiratory pressure during magnetic stimulation and found that Pmo,tw during a gentle exhalation from FRC showed excellent agreement with Poes,tw. We think, therefore, like HAMNEGARD et al [8], that transmission of pressure to the upper airways is not hindered by glottis closure with this technique. The increased variability that we ob-served could have resulted from technical errors during the magnetic stimulation.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In a preliminary study, we compared Poes,tw, considered as reference, to three noninvasive measurements of inspiratory pressure during magnetic stimulation and found that Pmo,tw during a gentle exhalation from FRC showed excellent agreement with Poes,tw. We think, therefore, like HAMNEGARD et al [8], that transmission of pressure to the upper airways is not hindered by glottis closure with this technique. The increased variability that we ob-served could have resulted from technical errors during the magnetic stimulation.…”
Section: Discussionmentioning
confidence: 95%
“…The Pmo,tw during gentle exhalation presented the best agreement with Poes,tw in all subjects. HAMNEGARD et al [8] also concluded that glottis closure can be avoided with this technique.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations